2009
DOI: 10.3111/13696990903479199
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of compliance to treatment with antidiabetes medication in type 2 diabetes mellitus: a review paper

Abstract: Improved compliance may lead to reductions of the total healthcare costs in T2DM, Further research is needed in countries other than the US to assess impact of compliance and persistence to pharmacotherapy on T2DM costs in country-specific settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
50
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 27 publications
2
50
0
4
Order By: Relevance
“…Qualitatively similar results have been shown in Europe (9). In addition to the negative impact on achieving effective glycemic control, poor medication adherence results in increased health care costs (1,2). Therefore, it stands to reason that in order to reduce the overall burden of diabetes, it is critical to address the issues of poor medication adherence.…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Qualitatively similar results have been shown in Europe (9). In addition to the negative impact on achieving effective glycemic control, poor medication adherence results in increased health care costs (1,2). Therefore, it stands to reason that in order to reduce the overall burden of diabetes, it is critical to address the issues of poor medication adherence.…”
supporting
confidence: 61%
“…Although numerous drugs are available for individualized management of type 2 diabetes, poor treatment adherence, suboptimal efficacy, inadequate weight control, and unacceptable tolerability remain barriers to glycemic control (1)(2)(3). Glucagonlike peptide 1 receptor agonists (GLP-1 RAs) are considered effective therapeutic agents for the treatment of type 2 diabetes (4) that lower glucose, promote weight loss, and have a low risk of hypoglycemia (5) due to their glucose-dependent effect on insulin secretion (6).…”
mentioning
confidence: 99%
“…Adherence to antidiabetic medications has been shown to improve glycaemic control, which augurs well for the long-term prognosis of the disease 13,14 . Medication adherence to antidiabetic agents has also been shown to be more cost-effective, as it may reduce hospitalization frequency and costs associated with both short-and long-trem complications 15,16 . Some of the reasons or predictors of poor adherence found in the literature include high pill burden, complexity of drug regimens forgetfulness, high cost of medications, presence or perceived fear of adverse effects, and poor knowledge about the disease condition [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Medication adherence to antidiabetic agents has also been shown to be more cost-effective, as it may reduce hospitalization frequency and costs associated with complications. 15,16 Worldwide, studies on medication adherence among diabetic patients have shown a wide variation. [17][18][19][20][21][22][23][24] In India, [25][26][27] Limited studies from Southern and Northern regions of India have documented wide variation in the medication adherence and have addressed the issues of nonadherence in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%